Behaviour of phytocenoses and herbage production regarding variation of top soil fertility in pasturelands of national parks in Mediterranean environments - Martiniello P.; Ciceretti C.; Sabia E.; Pacelli C.; Terzano M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In the last decade, because of the large needs of biomass for animal feeding, the sward of pasturelands were subject to stress. The application of chemical compounds was the agronomic approach used for restoring the ancient agropastoral and ecological activity of pasturelands. The aims of the study were to assess the effect of nitrogen-phosphorous fertilizer on biomass, herbage quality, flora composition and soil fertility in four Italian protected pastures of National Parks in Mediterranean environments. The results of the study show the efficiency of fertilisation to increase qualitative and quantitative herbage production, topsoil fertility and to minimize the variation of natural flora in the sward.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)